Modernizing Government budget administration: the application of technical cooperation in improving budget administration in the Governments of developing countries. - Public Administration Service (Washington: Agency for International Development, 1962)
This book seek identify key problems in efforts to modernizing government budget administration in developing countries.
asm; 25/01/19
Loans
Keywords: Budget; Developing countries